Comparison of Prevalence of Hypertension and Medical Expenses According to the Level of Physical Activity of Korean Adults - Byung Kun Lee (Asian Society of Kinesiology, 2018)
OBJECTIVES The purpose of this study is to compare the differences in the prevalence of hypertension in relation to the physical activity grade and to analyze differences in the days of hospitalization of hypertension patients, drug expenses and personal medical expenses. METHODS The Korea medical panel data was used in 2016, with a total of 13,276 adults and 3,470 hypertension patients. Physical activity was measured with IPAQ and converted to MET-minutes per week. The days of hospitalization, monthly average for hypertension drug expenses, and personal medical expenses were investigated, and frequency analysis, logistic regression, and ANOVA were performed. RESULTS The prevalence of hypertension based on the inactive group were decreased both minimally active group (odds ratio [OR] = 0.89) and the active group (OR = 0.77, p<0.01). The days of hospitalization, drug expenses, and personal medical expenses for hypertension were all significantly different among each physical activities group (p<.01). Days of Hospitalization and medical expenses have increased by 4.1 to 28.6 % in minimally active group compared with active group, while inactive groups have increased by 23.6 to 65.7 %, increasing more rapidly in inactive groups. CONCLUSIONS The prevalence of hypertension was further reduced in the order of minimally active and activity groups compared to inactive groups, and it makes lower the medical use and medical expenses associated with the level of physical activity of hypertension patients.